Game-Based Interactive Media Innovation in Arabic Language Learning: The Effectiveness of STAD-Based Digital Escape Rooms on Students' Learning Interests - Naili Hajar Illiyyun; Syarifuddin; Nurrokhmatulloh (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2026)
This study aimed to examine the effectiveness of integrating a Digital Escape Room with the Student Teams Achievement Division (STAD) cooperative learning model in improving students' interest in learning Arabic at MTs Ma'arif Sukorejo. The study employed a quasi-experimental design using a pretest–posttest control group design, involving 58 eighth-grade students divided equally into an experimental group (n = 29) and a control group (n = 29). In the experimental class, students learned Arabic through collaborative STAD activities integrated with Digital Escape Room challenges developed using the Genially platform, whereas the control class received conventional instruction. Data were collected using a learning-interest questionnaire covering students' enjoyment, interest, attention, and active participation, supported by observation, interviews, and documentation. The questionnaire demonstrated high reliability with a Cronbach's Alpha coefficient of 0.884. Data were analyzed using prerequisite tests, an Independent Samples t-test, and the Normalized Gain (N-Gain) test through IBM SPSS Statistics 27. The Independent Samples t-test, conducted on the posttest scores, revealed a significant difference between the experimental and control groups (p < 0.001). Furthermore, the experimental group achieved an average N-Gain score of 40.42% (moderate category), whereas the control group obtained −12.30%, indicating no meaningful improvement. These findings demonstrate that integrating the STAD cooperative learning model with Digital Escape Room media provides a more effective learning experience for enhancing students' interest in learning Arabic than conventional instruction. Keywords: Digital Escape Room, STAD, learning interest, Arabic language learning, game-based learning.